2020
DOI: 10.1002/cbdv.202000442
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Biological Evaluation of Xanthone Derivatives for Possible Treatment of Alzheimer's Disease Based on Multi‐Target Strategy

Abstract: Four xanthone derivatives were synthesized and evaluated as acetylcholinesterase inhibitors (AChEIs) with metal chelating ability and antioxidant ability against Alzheimer's disease (AD). Most of them exhibited potential acetylcholinesterase (AChE), butylcholinesterase (BuChE) inhibitory, antioxidant and metal chelating properties. Among them, 1-hydroxy-3-[2-(pyrrolidin-1-yl)ethoxy]-9H-xanthen-9-one had the highest ability to inhibit AChE and displayed high selectivity towards AChE (IC 50 = 2.403 � 0.002 μM fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Among the derivatives, the most potent inhibitor of AChE was compound ( 16) (4-bromo-1,3,6-trihydroxy-2,8-diisopentyl-7-methoxy-9Hxanthen-9-one) while compound (5) (2-(2,3-dihydroxy-3-methylbutyl)-1,3,6-trihydroxy-8-isopentyl-7methoxy-9H-xanthen-9-one) was the most potent inhibitor of BuChE with IC 50 values of 5.26 μM and 7.55 μM, respectively [31]. Similarly, a recent report by Yang et al [32] showed that among four xanthone derivatives that were synthesized, compound 3-(2-( pyrrolidinyl)ethoxy)-1-hydroxy-9Hxanthen-9-one showed the highest AChE inhibitory activity and high specificity for AChE (IC 50 = 2.403 µM) in comparison with BuChE (IC 50 = 31.221 µM) [32].…”
Section: Inhibition Of Acetylcholinesterase Activitysupporting
confidence: 58%
“…Among the derivatives, the most potent inhibitor of AChE was compound ( 16) (4-bromo-1,3,6-trihydroxy-2,8-diisopentyl-7-methoxy-9Hxanthen-9-one) while compound (5) (2-(2,3-dihydroxy-3-methylbutyl)-1,3,6-trihydroxy-8-isopentyl-7methoxy-9H-xanthen-9-one) was the most potent inhibitor of BuChE with IC 50 values of 5.26 μM and 7.55 μM, respectively [31]. Similarly, a recent report by Yang et al [32] showed that among four xanthone derivatives that were synthesized, compound 3-(2-( pyrrolidinyl)ethoxy)-1-hydroxy-9Hxanthen-9-one showed the highest AChE inhibitory activity and high specificity for AChE (IC 50 = 2.403 µM) in comparison with BuChE (IC 50 = 31.221 µM) [32].…”
Section: Inhibition Of Acetylcholinesterase Activitysupporting
confidence: 58%
“…Several studies have suggested that Cu, Fe, and Zn ions (especially Cu 2+ ) could promote Aβ aggregation to lead the neurotoxicity in AD patients [54] . Therefore, the chelating capacity of compound 3g to biometal ions (Cu 2+ , Fe 2+ , Zn 2+ , Na + , K + , Ca 2+ , and Mg 2+ ) was performed by UV‐vis spectrophotometer [55] . The UV spectrum of compound 3g in ethanol alone depicted maximum absorption at about 435 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[54] Therefore, the chelating capacity of compound 3g to biometal ions (Cu 2 + , Fe 2 + , Zn 2 + , Na + , K + , Ca 2 + , and Mg 2 + ) was performed by UV-vis spectrophotometer. [55] The UV spectrum of compound 3g in ethanol alone depicted maximum absorption at about 435 nm. When adding CuSO 4 , there was a significant red shift to 561 nm (shown in Figure 2A), which indicated that Cu 2 + could bind to compound 3g to form the complex 3g-Cu 2 + .…”
Section: Metal Chelating Properties Of Compound 3gmentioning
confidence: 99%
“…As shown in Figure 2, the nitrogen atom on the Schiff base and the oxygen atom on the 4‐hydroxy substituent of coumarin were separated by three carbon atoms and could be used as chelating sites to form stable six‐membered rings when coordinating with metal ions. Tertiary amine groups were introduced to improve the lipid water partition coefficient and the anti‐ChE abilities as was supported by previous works of our group [19–23] . The aromatic skeleton of coumarin was postulated to provide inhibition activity of Aβ aggregation as it might form π‐π interactions with the amino residues of the protein.…”
Section: Introductionmentioning
confidence: 85%